Understanding and treating HPV-associated oropharyngeal carcinoma: insights from a MedNewsWeek Keynote lecture by Dr Theodoros N. Teknos and literature review - Viviana Cortiana; Soumiya Nadar; Jade Gambill; Diksha Mahendru; Adhith Theyver; Helena S. Coloma; Chandler H. Park; Yan Leyfman (Therapeutic Advances in Medical Oncology)
Oropharyngeal carcinoma, a type of head and neck cancer (HNC), is an emerging malignancy associated with low survival rates. It typically affects older males and correlates with smoking, drinking, and lower socioeconomic conditions. Traditional treatments such as surgery have often yielded limited outcomes. However, recent insights, particularly those emphasized by Dr Teknos in his Keynote Conference at MedNews Week, have sparked a deeper exploration into alternative and more promising treatment methods. A comprehensive literature review was conducted to explore this subject further. One such approach, demonstrated by the UMCC 9921 trial, involves a comprehensive protocol starting with induction chemotherapy. This initial phase aims to reduce tumor burden and assess response to treatment. Based on the individual outcomes, patients then undergo concurrent chemoradiation or salvage surgery. This strategy has significantly improved survival rates, especially in human papillomavirus (HPV)-positive patients, showcasing the potential of tailored treatments. While these advancements are promising, long-term complications such as dysphagia and osteoradionecrosis remain a cause of concern. The rise of HPV-related head and neck squamous cell carcinoma has further changed how risk factors and treatment outcomes are viewed. HPV-positive cancers have unique characteristics and respond well to modern therapies. Researchers are investigating biomarkers such as circulating HPV DNA and immunoglobulin J polypeptide expression, which could provide valuable insights into disease progression and pave the way for more targeted and effective treatment strategies. In addition, the use of existing medications, such as fenofibrate, to combat HPV infections illustrates the resourcefulness in repurposing specific treatments. Challenges persist, especially in the need for reliable biomarkers for early disease progression detection and monitoring. Deeper insights into viral-host interactions shape promising immunotherapy strategies that could revolutionize treatment approaches. Collaborative efforts between researchers, healthcare providers, and policymakers play a vital role in translating these advancements into substantial clinical benefits, improving outcomes and quality of life for individuals affected by HPV-related diseases. While HPV-associated HNCs present significant challenges, continuous research and innovative treatments offer hope for a brighter future in combating this growing epidemic and improving patient care.